Evaluación del material celulósico proveniente de residuos derivados de la agroindustria del maíz (Zea Mays), para el proceso de elaboración de cartón - Rendón Pozo, Ariana Valeria (2021)
The need to find alternatives to the production of paper and cardboard with woody material has been one of the motivations for carrying out this research project. Our planet is currently immersed in different environmental problems that cause the deterioration of air, soil and water, for this reason it is important to identify the factors that contribute to this problem. As maize is one of the cereals with the highest production (850 million tonnes) and consumption (1,132 tonnes) worldwide, and as it is one of the crops that generates the greatest amount of agro-industrial waste, it was decided to use three types of waste derived from it, stalk, leaves and corn, to make cardboard from these raw materials, thus providing an alternative use to the creation of fertiliser and the burning of waste in the fields. To obtain cellulose pulp, two methods were used, the James Wise and Kurshner and Hoffner methods, which made it possible to obtain a final product with acceptable physical and mechanical characteristics that can compete with cardboard derived from woody material. In this research, the following variables were analysed: pH, humidity, tensile strength, porosity, ash, thickness, grammage, to establish how the use of different types of waste (Factor A: a0=stalk, a1=corncob, a2=leaves) influences the production of paperboard and the methods of obtaining cellulose pulp (Factor B: b0=Jayme Wise method; b1=Kurshner Hoffner method) were also analysed to determine which of these is better. The yield was also determined to establish which raw material provides a higher amount of cellulose pulp and a higher grammage in the paperboard. Statgraphics was used for the analysis of variance, Infostat was used for the significance tests and Statistica was used for the box plots. The results obtained made it possible to analyse the physical, chemical, and mechanical characteristics of the final product to establish whether the use of corn residues is an ideal alternative for the manufacture of cardboard, giving favourable results for most of the variables that were analysed. xii Finally, it is concluded that in obtaining pulp by the Kurshner and Hoffner method, Elote is the residue that provides the greatest amount of grammage in the 82g/m2 sheets of cardboard, this being the best treatment (a2b1). Keywords: Waste, Fiber, Cardboard, Cellulosic pulp